Characterization of rhizospheric bacteria isolated from soil cultivated with sugarcane in Tamaulipas state, Mexico - García Olivares, Jesús Gerardo; Reyes Lara, Martín Abraham; Flores Gracía, Juan; Quiroz Velásquez, Jesús Di Carlo; García León, Israel; Reyes Hernández, José; Gill Langarica, Homar Rene (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2021)
The state of Tamaulipas, Mexico, has two important sugar mills, with plantations of sugarcane (Saccharum officinarum L.) of more than 50 years, the objective of the study was the identification and bacterial characterization in the production of indole-3-acetic acid (IAA), the solubilization of phosphorus and plant growth of bacterial isolates from the rhizosphere of sugarcane. The isolation and morphological characterization were in 30 rhizosphere soil samples of the sugarcane variety CP 72-2086 using the Luria-Bertani media, Congo Red Agar and Potato Dextrose Agar. The molecular characterization was with the 16S rRNA gene and the bacterial inoculation consisted of seedlings of the variety CP 72-2086. 121 strains (38 species) were isolated, being Bacillus sp. most frequently, 14 species were positive for phosphorus solubilization: Bacillus sp. (6), Pseudomonas spp. (5), Paenibacillus (2) Streptomyces venezuelae (1) stand out. The greater phosphorus solubilization was Pseudomonas mediterranea (21.6 mm). Nine bacteria showed production close to 5 ppm IAA: Bacillus aryabhattai (6 ppm), Bacillus pumilus (5.8 ppm) and Ensifer adhaerens (5.6 ppm). Bacillus megaterium showed a higher percentage of chlorophyll and foliar nitrogen. In the present analysis, 38 bacterial species associated with the rhizosphere of the sugarcane variety CP 72-2086 were identified, so these results showed the potential to select native bacteria that have the ability to stimulate plant growth of the variety CP 72-2086.